2002
DOI: 10.1046/j.1365-2214.2002.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

A dose–response relationship between short sleeping hours and childhood obesity: results of the Toyama Birth Cohort Study

Abstract: A strong inverse association was observed in the relationship between sleeping hours and childhood obesity. Longitudinal research will be required to confirm this causality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
266
7
21

Year Published

2005
2005
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(325 citation statements)
references
References 29 publications
(37 reference statements)
26
266
7
21
Order By: Relevance
“…Similar findings have also been reported in children in the US and Japan indicating an inverse relationship between daily sleeping hours and risk of childhood obesity. 8,9 In our present study, we observed a clear inverse trend between daily sleeping hours and BMI, reaching statistical significance in men.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar findings have also been reported in children in the US and Japan indicating an inverse relationship between daily sleeping hours and risk of childhood obesity. 8,9 In our present study, we observed a clear inverse trend between daily sleeping hours and BMI, reaching statistical significance in men.…”
Section: Discussionsupporting
confidence: 65%
“…5,6 Recently, there are increasing number of reports on the association between short daily sleeping time and obesity. [7][8][9] These observations have led to the hypothesis that metabolic and hormonal changes associated with stressful lifestyle such as inadequate sleep might affect the body weight. 7,10 In support of this notion, stress-induced hypercortisolemia can lead to obesity and decreased insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…This finding of growth limitation in obesity has only ever been reported in developing countries, such as Brazil, 12 and may point to the increasing availability of inexpensive, energy-dense low-nutrient food as being a substantial cause of the increasing epidemic of obesity in this social group. However, other socioeconomic-linked factors including tobacco smoke exposure 13 (in utero and postnatal), decline in physical activity, 14 and possibly sleep patterns 15,16 may play important roles in growth and obesity. Indeed, a major impact on growth and body fat in children is growth hormone release, which shows peaks of secretion during sleep, following feeding and exercise.…”
Section: Resultsmentioning
confidence: 99%
“…12 Other potential mediating variables could include increased exposure to food-related advertising directed at children, 42,43 or interference with sleep. Two studies have demonstrated that children who receive less than 10 h of sleep per night were more likely to be obese, 44,45 and additional research has shown that having a TV in the bedroom is associated with fewer hours of sleep. 9 To reduce child overweight status, successful interventions have included limiting the amount of time spent in front of the television.…”
Section: Discussionmentioning
confidence: 99%